COMMUNITY SERVICE FOR ECONOMIC INDEPENDENCE OF JOINT BUSINESS GROUPS BASED ON SURABAYA CITY'S DIGITAL - Indriastuty, Dwi Elok; Priyambudi, Surya; Indrawati, Trisa (Universitas Pelita Harapan, 2024)
The partners are Micro, Small, and Medium-sized Enterprises (MSMEs) located in Babat Jerawat Village, Pakal District, Surabaya City. In light of the aforementioned background, the following issues have been identified: 1) Partners lack an understanding of food safety; 2) Product packaging is still not appropriate; 3) The use of production equipment is still lacking and traditional; 4) Processed cake products are only limited; 5) Partners do not maintain financial records in a proper and periodic manner; 6) In marketing, they do not utilize social media and eCommerce; and 7) There is a lack of attractive photo design for marketing. The program's objectives are as follows: 1) To increase the amount of product capacity, quality, and hygiene; 2) To increase product turnover; 3) To improve financial and business management; 4) To increase innovation to produce a new product; and 5) To expand product marketing areas. The implementation method commences with the following steps: 1) Team socialization with MSME partners; 2) Training in the fields of production, business management, and marketing is then implemented; 3) Appropriate technology is applied to MSME partners; 4) Assistance and evaluation are provided to MSME partners; and 5) Program sustainability is then addressed. The results of the activities are as follows: 1) Partners have demonstrated an increased understanding of food safety, sanitation, and personal hygiene; 2) Partners have obtained NIB and Halal certificates; 3) Partner production capacity has increased by 40%; 4) Partners have developed skills in the production of innovative processed cake products; 5)Partner turnover has increased by 25%; 6) Enhancement of partner competencies in the domain of routine financial documentation; 7) Availability of financial, social media, and eCommerce applications; 8) Elevation of partner abilities pertaining to the dissemination of information through social media, eCommerce, product photos, and product video content.